2016
DOI: 10.1152/ajpcell.00236.2016
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the mitochondrial calcium uniporter in cardiac myocytes improves impaired mitochondrial calcium handling and metabolism in simulated hyperglycemia

Abstract: Diabetic cardiomyopathy is associated with metabolic changes, including decreased glucose oxidation (Gox) and increased fatty acid oxidation (FAox), which result in cardiac energetic deficiency. Diabetic hyperglycemia is a pathophysiological mechanism that triggers multiple maladaptive phenomena. The mitochondrial Ca uniporter (MCU) is the channel responsible for Ca uptake in mitochondria, and free mitochondrial Ca concentration ([Ca]) regulates mitochondrial metabolism. Experiments with cardiac myocytes (CM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 58 publications
(84 reference statements)
4
50
1
Order By: Relevance
“…Recently, the pathophysiological role of MCUC in diabetes has become a topic of investigation. We previously reported that MCU protein levels and [Ca 2ϩ ] m were decreased in diabetic mice (34), and have confirmed these results here. In addi-tion, we observed diminished mitochondrial Ca 2ϩ uptake and mitochondrial Ca 2ϩ content in diabetic CM.…”
Section: Mcu Improves Cardiac Metabolism and Function In Diabetessupporting
confidence: 92%
See 2 more Smart Citations
“…Recently, the pathophysiological role of MCUC in diabetes has become a topic of investigation. We previously reported that MCU protein levels and [Ca 2ϩ ] m were decreased in diabetic mice (34), and have confirmed these results here. In addi-tion, we observed diminished mitochondrial Ca 2ϩ uptake and mitochondrial Ca 2ϩ content in diabetic CM.…”
Section: Mcu Improves Cardiac Metabolism and Function In Diabetessupporting
confidence: 92%
“…Our findings show decreased MCU protein levels, corresponding to reduced MCU mRNA levels (Ϫ50%). Hyperglycemia may be a contributing factor to MCU down-regulation in a STZ-induced diabetic model because we have previously demonstrated that exposing cultured neonatal CM to hyperglycemia leads to markedly decreased MCU levels (34).…”
Section: Mcu Improves Cardiac Metabolism and Function In Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“…; Diaz‐Juarez et al . ), translational (Zaglia et al . ), and post‐translational regulation (Joiner et al .…”
Section: The Mitochondrial Ca2+ Uniporter Complex (Mcu)mentioning
confidence: 99%
“…Indeed, the MCU is identified by screening the binding proteins of its regulator, mitochondrial Ca 2+ uptake protein 1 (MICU1), which contains canonical EF-hand Ca 2+ binding domains (Perocchi et al 2010). Regulation of MCU channel activity is mainly achieved by its associated proteins (see below), although transcriptional (Marchi et al 2013;Diaz-Juarez et al 2016), translational (Zaglia et al 2017), and post-translational regulation (Joiner et al 2012;O-Uchi et al 2014) of the MCU have also been reported. The channel activity can be inhibited by Ruthenium Red, Gd 3+ , or site-specific mutagenesis on two residues (D261, E264) in the loop region (De Stefani et al 2011).…”
Section: The Mitochondrial Ca 2+ Uniporter Complex (Mcu)mentioning
confidence: 99%